PERLINDUNGAN HUKUM KONSUMEN TERHADAP PENYALAHGUNAAN DATA PRIBADI DALAM TRANSAKSI E-COMMERCE DI INDONESIA - Sri Agustini; Miasiratni Miasiratni; Widya Yoseva (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The growth of e-commerce transactions in Indonesia has increased the collection and processing of consumers’ personal data, which also creates risks of data misuse by business actors and third parties. This study aims to analyze the legal framework governing consumer protection against the misuse of personal data in e-commerce transactions and to examine the forms of legal protection available to consumers in Indonesia. This research employs a normative juridical method using statutory and conceptual approaches. The data consist of primary, secondary, and tertiary legal materials analyzed qualitatively. The findings indicate that legal protection of consumers’ personal data is regulated under Law Number 27 of 2022 on Personal Data Protection, Law Number 8 of 1999 on Consumer Protection, and Law Number 1 of 2024 concerning Information and Electronic Transactions. However, challenges remain in the implementation and enforcement of these regulations, particularly regarding the compliance of electronic system operators and consumer remedy mechanisms. Therefore, stronger supervision, law enforcement, and increased awareness among business actors and consumers are necessary to ensure effective personal data protection in e-commerce transactions.Keywords: consumer protection, personal data, e-commerce, legal protection.